UPAYA BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) KABUPATEN PELALAWAN DALAM MENANGGULANGI BENCANA BANJIR DI KECAMATAN PELALAWAN TAHUN 2018 - Pratiwi, Inggit Awalia; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The problem of flooding in Pelalawan District is caused by rainfall due to the accumulated garbage and the large amount of sand deposits in the sewer so that it rains the flow of water will be hampered. Weather factors and the influence of climate change that trigger the uncertain rainy season cannot be blamed but must be addressed by the government with program planning in tackling floods. BPBD is a regional apparatus of Riau Province which was formed in order to carry out its duties and functions to carry out disaster management. The BPBD implementing element is under and the responsibility of the BPBD coconut is led by the Chief Executive who assists the BPBD Head in carrying out the duties and functions of the BPBD implementing element.               This study aims to find out how the efforts of the Regional Disaster Management Agency (BPBD) of Pelalawan Regency in Overcoming Flood Disasters in Pelalawan District in 2018 and what are the inhibiting factors for the efforts of the Pelalawan Regency Regional Disaster Management Agency (BPBD) in Overcoming Flood Disasters in Pelalawan District in 2018 2018. The research location was conducted in Pelalawan BPBD Pelalawan Regency. Furthermore, data collection techniques were carried out by interviews, documentation and literature studies.               The results of this study are the efforts of the Regional Disaster Management Agency (BPBD) of Pelalawan Regency in Overcoming Flood Disasters in Pelalawan District in tackling flood disasters in Pelalawan District have not run optimally. This is caused by several factors such as lack of budget and lack of public awareness in littering. . Keywords: Countermeasures, and BPBD.